The additional phrases on a Genizah fragment of Bavli Eruvin 4b–5a - Zur, Uri (HTS teologiese studies, 2020)
This article deals with the additional phrases found in the Cairo Genizah fragment related to Bavli, Tractate Eruvin 4b–5a, identified as Cambridge UL T-S F1 (1) 44. FGP No. C 96446. Some of these additional phrases have not been found in any version of the various manuscripts and printed versions, and some were found in only one version. The purpose of the article was to examine whether these additional phrases preserve an ancient version that was only preserved in this Genizah fragment or whether they are a type of errors in the fragment. The conclusions of the article with regard to these additional phrases are varied; some of the phrases preserve an ancient version and some do not.